Role of the outer membrane protein A (OmpA) in the interaction of Acinetobacter bauamnnii with host cells. - Cabello Vega, Belén; Molina Panadero, Irene; Atalaya Rey , Celia; Younes Smani , Younes (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2024)
Background: In light of increasing antibiotic resistance the World Health Organization published a list of pathogens where Acinetobacter baumannii is considered as the most threatening Gram-negative bacteria (GNB). It is an GNB which is associated with hospital-acquired infections and its prevalence of multidrug-resistant strains is increasing. In addition, the identification of outer membrane protein A (OmpA) as a key bacterial virulence factor has been a major breakthrough (1). It is the most abundant and conserved porin asociated with A. baumannii virulence and survival (1,2). In this regard, the aim of this study is understanding OmpA mechanism of action in host- pathogen interaction that could be relevant as a therapeutic target in the future. Methods: To perform adhesion and invasion assays, HeLa cell line were infected with A. baumannii 17978 wild type strain and A. baumannii 17978 deficient in OmpA strain during 2 hours and incubated in CO2 at 37ºC. In invasion assay, gentamicin was added to kill extracellular bacteria. To observe autophagosome-lysosome machinery, labelling of lysosomes through inmunoassay was made when HeLa cell line is infected with A. baumannii 17978 wild type and A. baumannii 17978 dificient in OmpA during 2 hours. To demonstrate whether OmpA is involved in switching acid pH into neutral one as mechanism of resistance to lysosome, a growth curve with A. baumannii 17978 wild type and A. baumannii 17978 dificient in OmpA at pH 4.8 and 7,1 was performed. Results: A decrease in adhesion and invasive capacity of A. baumannii 17978 dificient in OmpA in HeLa cells was observed. Moreover, it was observed that a few number of lysosomes were activated when HeLa cells are infected with A. baumannii 17978 dificient in OmpA when compared with A. baumannii 17978 wild type strain. However, both A. baumannii 17978 and A. baumannii 17978 dificient in OmpA were able to switch acid pH into neutral one. Therefore, OmpA A had no significant role in acid pH nos obtenidos. No tienen porqué aparecer todos los apartados (se puede prescindir de alguno de ellos, o todos). No más de 2500 caracteres el total del resumen. Incluir aparte (en el apartado de debajo) 1-3 referencias bibliográficas. Conclusions: The results of the study show that OmpA is involved in bacterial adhesion and invasion with host cells. Moreover, it is the main factor involved in cell autophagosome-lysosome activation, which is one of the mechanism involved in the intracellular tr.